THE PROBLEMS AND GUIDELINES FOR INTEGRATION PROTECTION FOR DRUGS PROBLEM OF YOUTH IN SCHOOL - Dhanabhaddo (Tipwong), Phrasamu Thanapat; (Sakorn Sakaro), Phrakru Wutthisakorntham; Chimhad, Pairat (Journal of MCU Nakhondhat, 2023)
This article aims to present problems and integrated approaches to drug problem prevention. of youth in educational institutions, among students at the primary and secondary levels from the information it was found that There are 152,504 youths who are students in the at-risk group, 8,138 are in the drug users group, and 127 are in the dealer group, which shows that the drug problem situation in educational institutions is very serious. continuously violent. The most prevalent drug is methamphetamine, followed by ice, marijuana, and heroin. Affects the nervous system which is caused by 1) personal factors 2) family factors 3) environmental factors for solving past problems has created a drug-free white educational institution project. with the participation of executives the school board, parents, teachers, students, and community, however, encountered operational problems, namely inconsistent operations and a lack of concrete evaluation. Including solving problems that do not match the target group. Therefore, guidelines for prevention drug problems in educational institutions are as follows: 1) have a clear database 2) have network partners who are actively driving it 3) develop modern information systems 4) develop research and innovation 5) create appropriate alternatives, including providing. The importance of building immunity for children and youth by instilling good values ​​and attitudes towards oneself and society, encouraging children and youth to think critically and analytically. and build life skills needed to live happily to enable Thai children and youth to grow up to be quality citizens and stay away from drugs.